ASIAN HERMENEUTICS FROM A HISTORICAL PERSPECTIVE - MUNDADAN, A. MATHIAS (Asian Horizons, 2007)
In the second half of the 20th century hermeneutics (understanding the Word of God) began to witness a great shift-an explosion, an entirely new turn, a radical paradigm shift. The context is the emergence of the free, independent nations in the wake of the phenomenon of decolonization. These nations arose with a new awakening of their cultural identity, with a new self-consciousness. Together with this positive aspect of the present context, a negative phenomenon also began to grow - the phenomenon of "economic and technical colonialism," a "new imperialism." Even the word "globalization" is used in this context. The "Third World" theologians understand this term to mean "a phenomenon bound up with the growth and expansion of capitalism and the integration of national economies into its system